PERAN PENGABDIAN KEPADA MASYARAKAT (PKM) DALAM MEWUJUDKAN KASIH YANG MEMULIHKAN DI JEMAAT GMIST EFRATA BUHA - Rifke Alfione Pananggung; Monadeby Wogono (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service (PKM) is one of the main pillars of the Tridarma of Higher Education, serving as a bridge between the academic world and the real needs of society. This article aims to examine the role of PKM in realizing "restoring love" within the GMIST Efrata Buha Congregation. The method used is a participatory and contextual approach, involving the congregation as both the subject and active partner in every stage of the activity, ranging from needs identification, planning, implementation, to evaluation. PKM activities were carried out through various programs, including seminars, counseling and spiritual therapy services, holistic health assessments, and faith-building worship services. The results of the activities indicate that PKM not only provides practical benefits, but also has a transformative impact on the spiritual, psychological, social, and relational aspects of the congregation. The positive responses from the pastor, church council, and congregation demonstrate that these activities are relevant and contextual in addressing the needs of the congregation. Thus, PKM can serve as an effective means of delivering holistic and sustainable ministry, as well as being a tangible expression of restoring love in the life of the congregation.